Auditorias operacionais ambientais realizadas pelo Tribunal de Contas do Estado do Paraná: efetividade no monitoramento e contribuições para o desenvolvimento local/regional - Albuquerque, Cristhian Carla Bueno de (2022)
The environment is constitutionally enshrined in Brazilian law as a fundamental right, a good for the common use of the people and essential to the quality of life of the community, imposing on the public power and society to guarantee, through its defense and preservation, the sustainable development for present and future generations. In order to guarantee this greater good, the same Constitution gave the Audit Courts the power to control and inspect environmental assets, which is exercised through environmental operational audits. This type of audit is the most appropriate instrument for this purpose, since it has the scope to verify the efficiency, effectiveness and economy of environmental actions, ensuring the performance and improvement of environmental management, encouraging the dialogue of external control institutions with the audited entities. They can optimize the results of environmental actions for society, identifying good practices and opportunities for improvement. Configuring an evolution of the way of proceeding of these external control institutions, previously focused only on accounting and compliance audits (legality of procedures). This Thesis proposes the adoption of measures aimed at improving the monitoring processes of these audits, só that they become more effective and can contribute to the sustainable development of the municipalities and/or region where the audited entity/organisation is located. To this end, an exploratory research was carried out through bibliographic, documentary research and theoretical-empirical observation, based on descriptive data analysis, on the procedures carried out at the Court of Auditors of the State of Paraná, from 2009 to 2021, through which it appears that there are few in-depth studies on the subject addressed, and, although the Court of Auditors of Paraná has important initiatives for the purpose of strengthening environmental operational audits, such as the pioneering spirit in the implementation of the Sustainable Development Goals in the State of Paraná, its performance is still too low, reaching less than 25% of the municipalities in Paraná during the period studied. There are also flaws in the procedures, such as the absence of internal rules standardizing the Court’s performance in environmental audit processes and in their respective monitoring, generating excessive bureaucratization of processes, lack of transparency of audit activities and distortion of the type of audit. Concerning the material aspect there is a lack of participation of relevant actors in the process, such as the Legislative Power and the Internal Control body, and that the focus of these audits revolves around strictly operational issues, aimed at short-term planning. In view of this scenario, it is concluded that institutional engagement is necessary for the improvement and strengthening of this type of audit, in view of the benefits it can provide to society, whose reports must have broad access both to the community and to the Legislative Power, important actors. In this process of environmental preservation and induction of public policies. In fact, transparency encourages discussion, criticism and relevant decisions. And, although these procedures currently do not generate impacts tending to directly corroborate the sustainable development of the region where the audited entities/agencies are inserted, not even the audited Municipality, they are fertile arenas for the elaboration of situational strategic planning (PES) aimed at solving more complex environmental problems, tending to generate significant contributions at local and regional levels. In this way, the participation of the Legislative Power, of the internal control body of the audited entity and of actors involved with the object of the audit are essential in these procedures, giving rise to greater institutional dialogue with a view to better results of environmental actions and public policies, defending and guaranteeing an ecologically balanced environment for present and future generations.